2017
DOI: 10.3390/ijgi6110339
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Spatiotemporal Patterns of Long-Distance Taxi Rides in Shanghai

Abstract: Floating Car Data (FCD) has been analyzed for various purposes in past years. However, limited research about the behaviors of taking long-distance taxi rides has been made available. In this paper, we used data from over 12,000 taxis during a six-month period in Shanghai to analyze the spatiotemporal patterns of long-distance taxi trips. We investigated these spatiotemporal patterns by comparing them with metro usage in Shanghai, in order to determine the extent and how the suburban trains divert the passenge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 16 publications
(16 reference statements)
0
4
0
Order By: Relevance
“…Therefore, we can conclude from the above that most travel distances are less than 30 min for OCH, and thus, OCH may not be the best mode of transportation for long distances. When faced with a long-duration trip, people prefer to select other transportation modes instead of OCH given the higher cost ( 41 ). There are still some long-duration trips, however, which may result from the lack of other modes of transport or to avoid the traffic peak hours.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, we can conclude from the above that most travel distances are less than 30 min for OCH, and thus, OCH may not be the best mode of transportation for long distances. When faced with a long-duration trip, people prefer to select other transportation modes instead of OCH given the higher cost ( 41 ). There are still some long-duration trips, however, which may result from the lack of other modes of transport or to avoid the traffic peak hours.…”
Section: Resultsmentioning
confidence: 99%
“…There are still some long-duration trips, however, which may result from the lack of other modes of transport or to avoid the traffic peak hours. Those passengers are willing to choose OCH instead of the metro as their first priority, and their second concern is avoiding the metro’s inconvenience resulting from the interchanges ( 41 ).…”
Section: Resultsmentioning
confidence: 99%
“…These results suggest that urban functions and function mixes may influence the residential travel carbon emissions of taxis and hence commuting carbon emissions. However, some studies have shown that excessive travel distance may lead to a preference for using taxis to travel with a threshold value of 15 km [49], which is similar to the distance from the central city area to Xiasha Cheng. From the results of previous experiments and studies, we speculate that this phenomenon may be due, on the one hand, to the fact that Xiasha Cheng is located far from the main urban area and is a fully functional integrated new city with better jobs, housing, and functions.…”
Section: The Impact Of Urban Spatial Structure and The Construction O...mentioning
confidence: 99%
“…Through similarity measurements of trajectory data, valuable information can be mined from large collections of trajectories, such as traffic flows and hot routes [9,10]. It is very useful for many applications, such as urban hotspot detection [11,12], behavior model analysis [13,14], traffic monitoring and prediction [15][16][17], urban planning [18,19] and location optimization [20,21], etc. Advances in location-based applications are increasingly creating new, sophisticated mechanisms that can foster the exchanges of information among travels to provide better services and promote a sustainable economy.…”
Section: Introductionmentioning
confidence: 99%